ECONOMIC ASSESSMENT OF KASHMIR UNDER SIKHS 1819-1846 - Zumeer Ahmad Sofi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The beautiful valley of Kashmir has been named by people with different names. Some call it "Heavens on Earth," some call it "Switzerland of India," and the famous Mughal rulers called it "Paradise on Earth." The valley has remained an apple in the eyes of foreign invaders since the very past. Among all these foreign rulers, some were rude and some were soft. The 19th-century Kashmir witnessed the rule of Sikhs, which stretched over a vast area extending from Kashgar in the east to Punjab in the north, Khorasan in the south, and Afghanistan in the west. The Sikh rule was founded by Maharaja Ranjit Singh in 1819 and continued by his successors till 1846. These Sikhs ruled Kashmir in a turbulent way, and the people of the valley suffered a lot. They imposed high taxes on innocent peasants, leaving the land uncultivated. They implemented a beggar system, which resulted in people leaving the valley. During this period, the economy of the valley faced a decline as trade decreased, and cottage industries were shut down. These Sikh rulers drained the economic resources of the country, resulting in the valley during the Sikh rule presenting a picture of a desert due to exorbitant taxes and inhuman tyranny of Sikh rulers.